Tretinoin peel: a critical view - Juliana Mayumi Sumita; Gislaine Ricci Leonardi; Ediléia Bagatin (Sociedade Brasileira de Dermatologia, 2017)
Abstract The tretinoin peel, also known as retinoic acid peel, is a superficial peeling often performed in dermatological clinics in Brazil. The first study on this was published in 2001, by Cuce et al., as a treatment option for melasma. Since then, other studies have reported its applicability with reasonable methodology, although without a consistent scientific background and consensus. Topical tretinoin is used for the treatment of various dermatoses such as acne, melasma, scars, skin aging and non-melanoma skin cancer. The identification of retinoids cellular receptors was reported in 1987, but a direct cause-effect relation has not been established. This article reviews studies evaluating the use of topical tretinoin as agent for superficial chemical peel. Most of them have shown benefits in the treatment of melasma and skin aging. A better quality methodology in the study design, considering indication and intervention is indispensable regarding concentration, vehicle and treatment regimen (interval and number of applications). Additionally, more controlled and randomized studies comparing the treatment with tretinoin cream versus its use as a peeling agent, mainly for melasma and photoaging, are necessary.